2010
DOI: 10.1590/s0103-21002010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento da dor durante a instalação do cateter central de inserção periférica em neonatos

Abstract: Objective: To measure pain in neonates during placement of central line catheter via peripheral insertion by comparing pain at the moment of the introduction of the catheter and pain at the progression of the catheter. Methods: This was a descriptive exploratory study with 28 neonates from a large teaching hospital in Sao Paulo city. Data were collected with the Premature Infant Pain Profile (PIPP) 15 seconds prior the initial introduction of the catheter, during the initial introduction of the catheter (30 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 13 publications
0
9
0
17
Order By: Relevance
“…Assim, as reações comportamentais do RN em face da dor são promissoras para a sua avaliação, uma vez que representam uma resposta mais específica ao estímulo doloroso, quando comparadas aos parâmetros fisiológicos (15) . Neste estudo, observamos que em 95% (19) dos procedimentos, os RN apresentaram alteração da mímica facial, especialmente testa franzida e olhos espremidos. Estas reações comportamentais associadas às alterações fisiológicas (aumento da frequência cardíaca e diminuição da saturação de oxigênio) apresentadas pelos RN imediatamente após a aspiração traqueal, indicaram através dos escores da escala de PIPP, presença de dor.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Assim, as reações comportamentais do RN em face da dor são promissoras para a sua avaliação, uma vez que representam uma resposta mais específica ao estímulo doloroso, quando comparadas aos parâmetros fisiológicos (15) . Neste estudo, observamos que em 95% (19) dos procedimentos, os RN apresentaram alteração da mímica facial, especialmente testa franzida e olhos espremidos. Estas reações comportamentais associadas às alterações fisiológicas (aumento da frequência cardíaca e diminuição da saturação de oxigênio) apresentadas pelos RN imediatamente após a aspiração traqueal, indicaram através dos escores da escala de PIPP, presença de dor.…”
Section: Resultsunclassified
“…Um estudo realizado em 2008 com objetivo de avaliar o efeito da manobra de contenção durante a aspiração traqueal observou que este cuidado promove conforto, estabilização clínica e redução da dor nos neonatos (18) . Neste contexto, buscar estratégias para controlar a dor em neonatos deve ser uma meta para os profissionais de saúde, em especial estratégias não farmacológicas, com vista a aliviar a dor gerada por procedimentos clínicos e evitar o agravamento de seu estado de saúde (19) .…”
Section: Resultsunclassified
“…Five articles covered this category (Costa et al, 2013;Costa et al,2010;Onofre, Pereira &Peterlini, 2012;Fricke et al, 2005;Oliveira et al, 2014) that was divided into two subcategories: (1.1.) Nursing care related to pain management and (1.2.)…”
Section: Category 1: Nursing Care Using Picc Linesmentioning
confidence: 99%
“…Two articles reported about the measurement of pain and pain intervention during PICC insertion (Costa et al,2013;Costa et al,2010). The first article reported analgesic or sedative strategies adopted for the PICC insertion.…”
Section: Nursing Care Related To Pain Managementmentioning
confidence: 99%
“…The translated version needs to present semantic and idiomatic equivalence, in addition to being culturally and conceptually adjusted in relation to the originally proposed instrument. The PIPP scale has been used in Brazil for clinical setting and research contexts, as demonstrated in some publications, [16][17][18][19] although no studies related to the translation, adaptation and validation of these instruments in the country were identified within the methodological rigor needed.…”
Section: Introductionmentioning
confidence: 99%